2021
DOI: 10.1136/bmjresp-2021-001038
|View full text |Cite
|
Sign up to set email alerts
|

Effect modification by age of the association between obstructive lung diseases, smoking, and COVID-19 severity

Abstract: IntroductionObstructive lung diseases (asthma and chronic obstructive pulmonary disease (COPD)) and smoking are associated with greater risk of respiratory infections and hospitalisations, but conflicting data exist regarding their association with severity of COVID-19, and few studies have evaluated whether these associations differ by age.ObjectivesTo examine the associations between asthma, COPD and smoking on the severity of COVID-19 among a cohort of hospitalised patients, and to test for effect modificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
(64 reference statements)
0
5
0
Order By: Relevance
“… 8 A 2021 study from Massachusetts General Hospital reported that asthma was associated with decreased COVID-19 severity, as measured by the WHO Clinical Progression Scale (CPS). 12 A 2022 study from the UK using primary care records found that more severe asthma (defined as regular inhaled corticosteroid use or a history of frequent exacerbations) was associated with severe COVID-19 outcomes (hospital and ICU admission). 6 Finally, another 2022 study from the UK Biobank reported that having a diagnosis of asthma was associated with a greater chance of COVID-19 hospitalization across all ages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 A 2021 study from Massachusetts General Hospital reported that asthma was associated with decreased COVID-19 severity, as measured by the WHO Clinical Progression Scale (CPS). 12 A 2022 study from the UK using primary care records found that more severe asthma (defined as regular inhaled corticosteroid use or a history of frequent exacerbations) was associated with severe COVID-19 outcomes (hospital and ICU admission). 6 Finally, another 2022 study from the UK Biobank reported that having a diagnosis of asthma was associated with a greater chance of COVID-19 hospitalization across all ages.…”
Section: Discussionmentioning
confidence: 99%
“…The available literature on asthma and COVID-19 outcomes is inconsistent [6][7][8][9][10][11][12][13][14][15] and, with one exception, 14 is based on data from the early (pre-delta) stages of the pandemic. Other limitations of prior studies include not considering the deployment of COVID-19 vaccines and not systematically examining possible effect modification by the severity of asthma.…”
Section: Introductionmentioning
confidence: 99%
“…In order to properly allocate scarce resources and to support clinical decisions during the COVID-19 pandemic, it is important to have an evidence-based record, derived from available epidemiological and clinical data on the comorbidity between NCDs and COVID-19 among African patients. This is of particular importance as in many African countries, the demography is characterized by a large proportion of young people and a lower prevalence of lifestyle risks (e.g., obesity and smoking), which may prevent against severe SARS-CoV-2 [ 18 , 19 , 20 , 21 ]. Furthermore, genetic differences in COVID-19 susceptibility may exist [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID- 19), is an illness caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [1]. The unprecedented spread of this infectious disease (pandemic) posed devastating effects on the health and well-being of people around the world, including Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, smokers are less likely to test positive. Similarly, there are conflicting reports regarding reduced and worsening risk (14,15). The effect of smoking on COVID-19 has been associated with increased mortality and disease severity.…”
Section: Introductionmentioning
confidence: 99%